Patterns, predictors and prognostic relevance of high-grade hematotoxicity after temozolomide or temozolomide-lomustine in the CeTeG/NOA-09 trial - Weller, Johannes Michael; Schäfer, N.; Schaub, C.; Tzaridis, T.; Zeyen, T.; Schneider, M.; Potthoff, A. L.; Giordano, Frank Anton; Steinbach, J. P.; Zeiner, P. S.; Kowalski, T.; Sabel, M.; et al. (Journal of neuro-oncology, 2023)
In the randomized phase III trial CeTeG/NOA-09, temozolomide (TMZ)/lomustine (CCNU) combination therapy was superior to TMZ in newly diagnosed MGMT methylated glioblastoma, albeit reporting more frequent hematotoxicity. Here, we analyze high grade hematotoxicity and its prognostic relevance in the trial population.